Cloud-Based Transportation Management System (TMS) Implementation for Distribution Efficiency in National E-Commerce - Kasrim; Berilian Ayu Kusuma; Isah Fitriani (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the implementation of a cloud-based Transportation Management System (TMS) in enhancing distribution efficiency within Indonesia’s national e-commerce sector using a Systematic Literature Review (SLR) approach. The adoption of cloud-based TMS has become an integral component of Indonesia’s digital logistics transformation, emphasizing efficiency, transparency, and sustainability. The findings indicate that TMS can reduce transportation costs by 15–25%, accelerate delivery times, and optimize route planning through real-time data integration. Economically, the system strengthens national competitiveness by improving productivity and fostering cross-sector collaboration among logistics providers, government bodies, and e-commerce enterprises. From a sustainability perspective, TMS contributes to carbon emission reduction and energy efficiency in transportation, aligning with the nation’s green logistics initiatives and net-zero emission targets. Nevertheless, its effectiveness remains dependent on digital infrastructure readiness, human resource competence, and policy support for cross-sector data interoperability. This research highlights that the successful adoption of cloud-based TMS requires collaborative governance and inclusive technological integration policies. Therefore, TMS serves as a strategic foundation for enhancing distribution efficiency, e-commerce competitiveness, and sustainable digital economic growth in Indonesia.